(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In this modern age concrete and cement mortar are abundantly used in construction. Large amount of industrial waste are generated and if these wastes are not correctly used it will cause negative impact , thinking about environment, concrete engineers are trying to find out some cementitious materials which will have more strengthening ability and less impact on environment than cement. During the processing of cement huge quantity of CO2 is discharged into the surroundings, so to find out the replacement for cement we are approaching towards the clean and pollution free atmosphere. In the same way, during this research work we are using waste paper sludge ash as supplementary cementitious material. The paper sludge which is the byproduct of paper mill which is obtained during the manufacturing and recycling of paper. By using of waste paper sludge in concrete as supplementary cementitious material also increases strength in the concrete like compressive, flexural and split tensile strength. The paper sludge ash is used in the concrete in different values from varying percentage of 2% to 10%. During the manufacturing of the concrete all the codes have been followed for mixing .In this manufacturing process cubes of size (150*150*150) mm and cylinders of (150*300) mm were made with the change in percentage of WPSA. The specimens which were casted were properly cured and all the tests were conducted on them. The test which was performed on the samples were split tensile, Flexural, Compressive strength, Normal consistency test etc. It has been observed and recorded that the strength of the samples was increasing with the addition of the waste paper sludge ash.